Reproducibility of MRI renal artery blood flow and BOLD measurements in patients with chronic kidney disease and healthy controls. Issue 5 (5th November 2013) - Khatir, Dinah S.; Pedersen, Michael; Jespersen, Bente; Buus, Niels H.
<x xml:space="preserve">Abstract</x> Purpose Determine the reproducibility of renal artery blood flow (RABF) and blood‐oxygenation level dependent (R2*) in patients with chronic kidney disease (CKD) and healthy controls. Materials and Methods RABF and R2* were measured in 11 CKD patients and 9 controls twice with 1‐ to 2‐week interval. R2* in the cortex and medulla were determined after breathing atmospheric air and 100% oxygen. Reproducibility was evaluated by coefficients of variation (CV), limits of agreements and intra‐class coefficient calculated by variance components by maximum likelihood modeling. Results Single‐kidney RABF (mL/min) for patients was: 170 ± 130 and 186 ± 137, and for controls: 365 ± 119 and 361 ± 107 (P < 0.05 versus patients), for first and second scans, respectively. RABF measurements were reproducible with a CV of 12.9% and 8.3% for patients and controls, respectively. Renal cortical R2* was: 13.6 ± 0.9 and 13.5 ± 1.2 in patients (CV = 8.0%), and 13.8 ± 1.6 and 14.0 ± 1.5 in controls (CV = 5.6%), while medullary R2*(s−1) was: 26.9 ± 2.0 and 27.0 ± 4.0 (CV = 8.0%) in patients, and 26.0 ± 2.4 and 26.1 ± 2.1 (CV = 3.6%) in controls, for first and second scans, respectively. In both groups R2* in medulla decreased after breathing 100% oxygen. Conclusion The reproducibility was high for both RABF and R2* in patients and controls, particularly in the cortex. Inhalation of 100% oxygen reduced medullary R2*. J. Magn. Reson. Imaging 2014;40:1091–1098. © 2013 Wiley Periodicals, Inc.